Unilateral Brachial Plexus Lesion Impairs Bilateral Touch Threshold - Ramalho, Bia Lima; Rangel, Maria Luíza; Schmaedeke, Ana Carolina; Erthal, Fátima Smith; Vargas, Claudia D. (Frontiers in Neurology, 2019)
Unilateral brachial plexus injury (BPI) impairs sensory and motor functions of the upper limb. This study aimed to map in detail sensory impairment both in the injured and the uninjured upper limb in BPI. Touch sensation was measured through Semmes-Weinstein monofilaments at the autonomous regions of the brachial plexus nerves, hereafter called points of exclusive innervation (PEIs). Seventeen BPI patients (31.35 years ±6.9 SD) and fourteen age-matched healthy controls (27.57 years ±5.8 SD) were tested bilaterally at six selected PEIs (axillary, musculocutaneous, median, radial, ulnar and medial antebrachial cutaneous [MABC]). The comparison between the control group and the BPI patients’ injured side showed a robust difference for all PEIs (axillary, p<0.0001; musculocutaneous, p<0.0001; median, p<0.0001; radial, p=0.0001; ulnar, p=0.0015; MABC, p=0.0004). Moreover, the comparison between the control group and the BPI patients’ uninjured side revealed a difference for the median (p=0.0074), radial (p=0.0185), ulnar (p=0.0404) and MABC (p=0.0328) PEIs. After splitting the sample into two groups in respect of the dominance of the injured limb, higher threshold values were found for the uninjured side of patients with BPI in the right dominant limb compared to the control group at the median (p=0.0456), radial (p=0.0096) and MABC (p=0.0078) PEIs. This effect was absent in patients with BPI in the left, non-dominant arm. To assess the effect of the severity of the sensory deficits of the injured limb in the alterations of the uninjured limb a K-means clustering algorithm was applied to the BPI group (k=2) resulting in two groups with less or more severe sensory impairment. The less severely affected patients presented higher thresholds at the median (p=0.0189), radial (p=0.0081), ulnar (p=0.0253) and MABC (p=0.0187) PEIs of the uninjured limb in comparison with the control group. The results showed, as expected, an expressive reduction in touch threshold in the injured limb, allowing precise mapping of the impairment caused by the BPI. Crucially, BPI also led to reduced tactile threshold in specific PEIs in the uninjured upper limb. These findings suggest a superordinate model of representational plasticity occurring bilaterally in the brain after a unilateral peripheral injury.